Enhanced growth performance and steviol glycosides content in stevia rebaudiana under elevated carbon dioxide - Abzar, A.; Sakimin, Siti Zaharah; Jaafar, Hawa Z. E.; Tajidin, Nor Elliza (Malaysian Society of Applied Biology, 2024)
In the current climate-changing scenario with a steadily rising CO2 concentration, there is a chance that crop performance will be affected in terms of growth, yield, and quality. Therefore, an experiment was conducted in a glasshouse using a randomized complete block design with four replications to investigate the effect of short and long-term elevated CO2 on growth performance and chemical markers of Stevia rebaudiana Bertoni. The CO2 in the glasshouse was gradually elevated from 400 ppm to 1800 ppm weekly. The plants were exposed to elevated CO2 for four months (T1), two months (T2), and one month (T3), while the control plants (T4) were grown under ambient CO2 (aCO2) levels to assess the effect of elevated atmospheric carbon dioxide (eCO2) on stevia crop growth performance and steviol glycosides content. The number of branches per plant, plant height, number of leaves per branch, and plant biomass were found to be significantly increased under eCO2 treatment over aCO2 treatment. The eCO2 increased photosynthetic rate by 46% for T1, 45% for T2, and 29% for T3 over control plants (T4) at 3rd month of planting. The enhancement in photosynthesis is attributed to an increase in stevioside; with a 33% increase for T1 28.83% for T2 and 11% for T3 over aCO2. Similarly, the rebaudiosides A were also significantly increased by 32.8% for T1, 25% for T2, and 15% for T3 compared to the control under aCO2. Based on our findings, we concluded that eCO2 levels positively influenced the growth, biomass, and glycoside content by enhancing the physiological performance of Stevia rebaudiana Bertoni.